Strategi Prone Position Dan Breathing Exercise Dalam Menurunkan Sesak Napas Pada Pasien Pneumonia: Strategy Of Prone Position And Breathing Exercise To Reduce Shortness Of Breath In Pneumonia Patients - Ledju, Asrial; Santoso, Shelfi Dwi Retnani Putri; Paju, Wanto (Jurnal Keperawatan Sumba (JKS), 2024)
Pneumonia is a significant health threat as it is frequently listed among the top ten leading causes of death. Some reports even indicate that pneumonia is the third leading cause of death after tuberculosis (TB). Common symptoms of pneumonia include cough and shortness of breath. To address the issue of shortness of breath in pneumonia patients, one solution is the application of prone positioning and breathing exercises. Objective: To describe the application of prone positioning and breathing exercises in reducing shortness of breath in pneumonia patients. Method: This descriptive case study included two respondents selected through purposive sampling. The criteria included patients diagnosed with pneumonia, aged 20-60 years, with a clear consciousness, hospitalized for at least three days, experiencing mild to moderate respiratory dysfunction, and without severe complications. Nursing care and the interventions of prone positioning and breathing exercises were conducted over three days. Results: After three days of nursing interventions, patient 1's respiratory rate decreased from 28 breaths per minute to 24 breaths per minute, with SpO2 reaching 98%. The patient felt relaxed and did not report shortness of breath. In patient 2, the respiratory rate decreased from 26 breaths per minute to 20 breaths per minute, with SpO2 also reaching 98%. The patient also felt relaxed and did not report shortness of breath. Conclusion: The application of prone positioning and breathing exercises can improve respiratory rates and reduce shortness of breath in pneumonia patients. This is because these interventions help enhance breathing, oxygen saturation, and lung function, thereby reducing the degree